Polarisation and Electrochemical impedance spectroscopy Studies on Date Palm Seed Extract as Green Corrosion Inhibitors for Carbon Steel in 0.5 M HCl Solution - Mohammed, Naba Jasim; Othman, Norinsan Kamil (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the function of the date plm seed (Phoenix Dactylifera) as a green corrosion inhibitor for carbon steel in 0.5 M HCl solution. The polarisation and Electrochemical Impedance Spectroscopy (EIS) methods were used to investigate inhibition efficiency, including the current density and resistance of the corrosion towards the carbon steel. As a result, Tafel polarisation displayed maximum inhibition efficiency at 900 ppm. The inhibition efficiency of 89.05% was observed from IES at 900 ppm, which subsequently decreased to 77.89% and 81% at the concentration levels of 1100 ppm and 1400 ppm respectively. In conclusion, date palm seed extract is an effective inhibitor t 250C and 900 ppm concentration level, and it could also be used to protect carbon steel from corrosion in an acidic medium